Genomic landscape in Saudi patients with hepatocellular carcinoma using whole-genome sequencing: a pilot study - Hassanain, Mazen; Liu, Yang; Hussain, Weam; Binowayn, Albandri; Barakeh, Duna; Alsolme, Ebtehal; AlSaif, Faisal; Almasaad, Ghaida; AlSwayyed, Mohammed; Alaqel, Maram; Aljunidel, Rana; Abdelrahman, Sherin; et al. (Frontiers in Gastroenterology, 2023)
Background and aims Hepatocellular carcinoma (HCC) is the third most prevalent cancer in Saudi Arabia. HCC poses a significant clinical challenge due to the presence of resistance among certain patients to the standard therapeutic agent sorafenib. This study aims to unravel the genomic characteristics of HCC patients in Saudi Arabia, investigate the genetic makeup of tumors in both sorafenib-sensitive and sorafenib-resistant patients, and analyze the functional implications of genomic abnormalities observed in these individuals. The resistance displayed by some HCC patients toward sorafenib underscores the need for alternative treatment approaches to effectively combat this formidable disease burden. Methods Whole-genome sequencing (WGS) was performed on 16 HCC samples and targeted sequencing was performed on seven additional tumors. We identified and validated somatic and germline genetic aberrations. Employing a prize-collecting Steiner tree algorithm, we identified important altered genetic modules and potential biomarkers for each patient. Furthermore, we analyzed non-synonymous germline and somatic mutations, specifically in patients who underwent sorafenib treatment. Results Out of the 13 patients who received sorafenib, three exhibited sorafenib sensitivity, while the others showed resistance to the drug. Notably, 3 out of 16 individuals carried cancer-predisposing mutations. Additionally, 8 out of 16 patients displayed non-synonymous somatic alterations in genes associated with cancer. In the targeted-sequencing samples, rare non-synonymous variants were observed across all seven cases. The study also revealed the presence of specific somatic aberrations, including TP53, PIK3CA, APOB, CTNNB1, DPYD, LRP1B, MYC, and NFE2L2, which were identified in two patients. Among the 42 genes linked to sorafenib treatment, 4 out of 10 resistant patients carried somatic non-synonymous variants. Furthermore, when analyzing the 5,000 genes most relevant to the 42 genes, 7 out of 10 resistant individuals exhibited rare non-synonymous germline variants. Interestingly, none of the three sorafenib-sensitive patients displayed any concerning variants in those genes. Conclusion Our findings indicate that most of the HCC patients possess cancer-related genetic variants, and the altered pathways in these patients exhibit similarities. Notably, resistant patients exhibit a higher frequency of aberrations in sorafenib-related genes than do sensitive patients. Specifically, 4 out of 10 resistant individuals demonstrated 13 somatic mutations, whereas none of the three sensitive patients exhibited any. Similarly, 7 out of 10 resistant patients possessed 30 germline mutations, while none were observed in the sensitive group (two-sided Fisher’s exact test; somatic: p=0.50, germline: 0.07). These results contribute to our understanding of the genetic landscape of HCC and highlight potential therapeutic targets that could aid in overcoming treatment resistance.